Evaluasi Penggunaan Obat Antihipertensi pada Penyakit Hipertensi Disertai Gagal Ginjal Kronik (ICD I12.0) Pasien Geriatri Rawat Inap di RSUD A.W. Sjahranie Samarinda pada Tahun 2012 dan 2013 dengan Metode ATC/DDD - Eko Yudha Prasetyo; Oetari Oetari; Tri Wijayanti (Fakultas Farmasi Universitas Setia Budi, 2015)
Hypertension is a trigger factor of chronic kidney disease. This disease requires a special incentive treatment in geriatrics patient.The complexity of therapy forcing the use of polypharmachy teraphy. Evaluation needs to be done with the aim of knowing description the typeof antihypertensive drugs used and the quantity of its use based methods Defined Daily Dose (DDD) and suitability compared with Standar Pelayanan Medis (SPM) and the JNC 7. This study was a descriptive study with retrospective data collection. The sample was medical record data regarding the use of antihypertensive drugs in hypertension with chronic renal failure in geriatric patients (ageâ‰¥ 60) hospitalization. The data collected includes classes and antihypertensive drug name, strength, frequency, duration of usage, length of stay. Then the data to be processed to determine the quantity of drug use in the ambulatory DDD and Drug Utilization (DU 90 %). The results of this study concluded that antihypertensive drugs included in the DU 90 % segment in 2012 were amlodipine (39.19%), furosemide (24.14%), captopril (14.14%), telmisartan (11.36%), valsartan (2.04%), and in 2013 were amlodipine (35.11%), furosemide (22.88%), captopril (18.80%), telmisartan (7.02%), valsartan (6.51%). Suitability based on SPM in 2012 (78.57%) and in 2013 (63.63%) and by the JNC 7 in 2012 (42.85) and 2013 (36,36%). There was no change in the pattern of use of antihypertensive drugs between 2012 and 2013.